Determination of the chlorophyll content of extracts from Piper marginatum Jacq leaves collected in Itacoatiara using UV-Vis spectrophotometry. (REMUNOM, 2024)
Medicinal plants are producers of various metabolites and substances,among which we can mention chlorophyll, which gives the green color to plantleaves. Among the botanical genera and botanical families used in scientificexperiments, the Piperaceae family and the Piper genus stand out. The genus Piperand the species Piper marginatum Jacq. which has a high chlorophyll content in itsleaves, which gives them a green color and this content is often not quantified andamong the techniques used to analyze the chlorophyll concentration, the UVSpectrophotometry technique stands out. -Vis. The objective of this work was todetermine the chlorophyll concentration of different extracts present in Pipermarginatum Jacq collected in Itacoatiara using the UV-Vis spectrophotometrytechnique. The leaves of Piper marginatum Jacq. were collected at UFAM Campus Iin Itacoatiara and were taken to the Chemistry laboratory where they were cleanedand subjected to the extraction process separately in solvents (water and ethanol).The extracts were filtered separately and stored in an amber bottle and kept at anappropriate temperature. The extracts were subjected to different types of tests:Chlorophyll content in UV-Vis, Refractivity, Electrical conductivity and pH. Theanalyzes were subjected to statistical testing using the SISVAR software for thetested parameters and the absorbances were analyzed using the SciDavis software.The results obtained evaluated that the best solvent for chlorophyll extraction wasethanol, however both extracts were stable during the tests. These results are anindication that the species is stable in both solvents, however additional tests must becarried out on the species.